The use of combination plant growth promoting rhizobacteria to control chili leaf curl disease in the field - Wiyono, Suryo; Hidayat , Sri Hendrastuti; Suryaningsih, Andika Septiana; Sobir, Sobir (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Plant growth-promoting rhizobacteria (PGPR) is a promising technology for controlling viral diseases, including pepper yellow leaf curl disease (PYLCD) of chili pepper caused by Begomovirus infection. The objectives of this research were to investigate the effectiveness of PGPR containing Pseudomonas fluorescens PF1 and Bacillus polymyxa BG25, as well as their combination with other protective agents, to control PYLCD under field conditions in an endemic region. The treatments consisted of a single application of PGPR (a mixture of P. fluorescens PF1 and B. polymyxa BG25), guano tea, endophytic fungus H5, and neem oil; combination of PGPR with guano tea, endophytic fungus H5, and neem oil; conventional pesticide that relies on synthetic chemical insecticide sprayed weekly; and untreated plots. The experiment was arranged in a randomized block design with four replications. Treatment with PGPR alone was able to delay disease onset by 2.25 weeks, but it caused only a slight reduction in disease incidence. The combination of PGPR + guano tea and PGPR + endophyte H5 provided the best results in controlling PYLCD. The combination of PGPR + guano tea and PGPR + endophyte H5 delayed disease onset by 2.75 weeks and 3.25 weeks, respectively, and reduced disease incidence with effectiveness rates of 52.72% and 52.08%, respectively. These two treatment combinations gave the best performance for plant growth and yield.